The ANALYSIS OF COMMUNITY KNOWLEDGE AND ANXIETY WITH THE PROVISION OF THE COVID-19 VACCINATION IN THE WORK AREA OF PUSKESMAS PARUNG BOGOR DISTRICT: ANALISIS PENGETAHUAN DAN KECEMASAN MASYARAKAT DENGAN PEMBERIAN VAKSINASI COVID-19 DI WILAYAH KERJA PUSKESMAS KECAMATAN PARUNG BOGOR - Fitriani, Dewi; Ardi, Ni Bodro; Fitriani, Dhia Diana; Hardianti, Tita (Ruang Ide Publisher, 2022)
Abstract In January researchers managed to identify the cause of this pneumonia, namely the novel coronavirus. WHO officially named this disease Covid-19 (Corona Virus Disease 2019) and the name of the virus was SARS-CoV-2 (Severe Acite Respiratory Syndrome Coronavirus 2). According to the Regulation of the Minister of Health of the Republic of Indonesia No. 84 of 2020, vaccines are carried out in stages with the aim of reducing the transmission/transmission of COVID-19, reducing morbidity and mortality due to COVID-19, achieving group immunity in the community and protecting the community from COVID-19 in order to remain socially and economically productive. Objective: To determine the relationship between the level of knowledge and public anxiety on the provision of Covid-19 vaccination in the working area of the Puskesmas Parung Bogor District in 2022. Research Methods: Using a quantitative approach with a cross sectional study design. The data collection instrument used a questionnaire with a sample size of 80 respondents. Research Results: More than half of respondents are male, namely 53%, Almost half of respondents with the last education level at SD are 32%, Almost half of respondents aged 46-55 years are 29%, Most of the respondents who are willing to vaccinate covid-19 by 91%, Most of the respondents with a good knowledge level of 79%, More than half of the respondents with a normal anxiety level of 54%. Conclusion: it can be concluded that Ho is rejected, which means that there is a significant relationship between the level of public knowledge about the provision of covid-19 vaccination with p-value = 0.004, there is also a significant relationship between the level of public anxiety about giving covid-19 vaccination with p-value = 0.000. Keywords: Knowledge Level; Anxiety Level; Willingness to Do Covid-19 Vaccination